ONLINE LOANS AND USURY: REFLECTIONS ON AL-QUR'ANIC VERSES ON CONTEMPORARY PHENOMENA - Muhammad Zainul Arifin Fahmi; Ach. Sofauzzad; Aria Panji Saputra; Devi Kusumawati (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
The development of online lending platforms in the modern era presents both financial opportunities and ethical challenges. While offering quick and easily accessible financial assistance, many online lending services are entangled in exploitative practices similar to usury (interest), which is strictly prohibited in Islam. This study examines the verses of the Al-Qur'an related to usury, particularly QS. Al-Baqarah [2]: 275–279, to evaluate the validity of online lending from an Islamic ethical perspective. This research employs a qualitative approach with content analysis of classical and contemporary exegetical literature. The results indicate that while online lending can address practical needs in modern society, its validity depends on whether it adheres to principles of justice, transparency, and the avoidance of exploitation. As a solution, this study proposes a Sharia-compliant digital financing system based on qard hasan (benevolent loan) or mudharabah/murabahah contracts. These models ensure that financial services remain affordable while adhering to ethical and religious standards. The article concludes that online lending is not inherently prohibited, but must be regulated and redesigned under the guidance of the Qur'an to protect the dignity and financial well-being of society in the digital age.